Enterprises supply chain management for development of business - Syamsiah Badruddin; Anny Nurbasari; M. Ariza Eka Yusendra; Paisal Halim; Andri Winata; EF Sigit Rochadi; Stefanus Rumangkit; Hartono Hartono; Meiyanti Widyaningrum; Rhini Fatmasari; Baharuddin Baharuddin; Donna Sampaleng (International Journal of Supply Chain Management, 2020)
Abstract-Institutional and social capital theories can help to understand how social enterprises can contribute and transform sustainable supply chains. This article introduces a framework that seeks to understand social enterprise and entrepreneurship capabilities in transforming institutions to strengthen supply chain sustainability and briefly gives some preliminary findings related to social capital and supply chains. Presently the social entrepreneurship has many areas to explore and having exceptionally golden opportunities to reform the business research. With this article an analytical model and business model is proposed for commercial entrepreneurship. It also works as a bridge between many communities and the industries. Here it is also presented a roadmap for the future scope of industrial development. In this study it is try to explain that how a social entrepreneurship can work by providing high end services and user demands and also refer to establish many new industries. The new findings and the upcoming possible demands of a user are focused by this article.